2018
DOI: 10.5267/j.ac.2017.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the problems with the current adoption of IFRS in the companies among India, China, Germany, Russia and Kenya

Abstract: Accounting information provides past and current financial information of an economic unit for business managers, potential investors, and other interested parties. Internally generated accounting information helps business managers with planning, controlling, and making decisions referred to as managerial accounting information. However, if the companies, which have adopted International Financial Reporting Standards (IFRS) globally, cannot generate the same information then the accounting practices need to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In India for instance, the government is yet to set a timeline for acceptance of IPSAS standards (Krishnan, 2016). In an article published by Ombati and Shukla (2018), the authors observed that although accrual disclosures are made in the country's public financial statements, the dominant method is a cash-based accounting. In Pakistan, most of the cash-based accounting is aligned with cash-based IPSAS framework which is applied by the national government.…”
Section: Adoption Of Ipsas In South Asiamentioning
confidence: 99%
“…In India for instance, the government is yet to set a timeline for acceptance of IPSAS standards (Krishnan, 2016). In an article published by Ombati and Shukla (2018), the authors observed that although accrual disclosures are made in the country's public financial statements, the dominant method is a cash-based accounting. In Pakistan, most of the cash-based accounting is aligned with cash-based IPSAS framework which is applied by the national government.…”
Section: Adoption Of Ipsas In South Asiamentioning
confidence: 99%